Radiometric Mapping for The Identification of Hydrothermally Altered Zones Related to Gold Mineralization in Ife–Ilesa Schist Belt, Southwestern Nigeria - Ayokunle Adewale Akinlalu (Indonesian Journal of Earth Sciences, 2023)
This study presents the interpretation of airborne gamma ray spectrometric data to delineate hydrothermally altered zones related to gold mineralization in the Ife–Ilesa Schist belt. K/eTh, Kd and F–Maps highlighting Potassic alterations related to gold mineralization were processed on the Oasis Montaj software and subsequently integrated using fuzzy logic modeling to produce the hydrothermal alteration map of the study area. The C–A fractal analysis was applied to the final hydrothermal map and was able to classify the study area into background, very low, low, moderate, high and very high alteration. These classes reflect the pervasive hydrothermal alteration style of the study area. The hydrothermally altered areas are evident on granitoids and areas proximal to it indicating that granitoids are proxies of heat source. Occurrence of active mining sites in the area agrees with the generated hydrothermal alteration map of the study area with 81% agreement. It therefore shows that radiometric method is a veritable method in mapping hydrothermal alteration areas. The use of radiometric method only cannot reliably map areas of gold mineralization as mineralization can be associated with several other processes. Hence, other methods involving geochemical and magnetic methods including GIS tools can be employed for further prospecting.